Comparative analysis of border cooperation between Russia and Asian countries (China, Mongolia, and the DPRK) ("Journal "U". Economy. Management. Finance.", 2025)
The article presents a comparative analysis of border cooperation between Russia and China, Mongolia, and the DPRK. It examines the features of trade and economic interaction, infrastructure development, and institutional mechanisms. The study identifies factors contributing to effective cooperation, as well as limitations hindering its development. Special attention is given to the strategic importance of the Russia–China partnership and the potential of the trilateral corridor “Russia–Mongolia–China.”
Keywords: border cooperation; Russia; China; Mongolia; DPRK; foreign economic relations; cross–border trade; infrastructure; economic corridor; international partnership